The influence of discount and bonus pack on impulse buying and hedonic shopping motivation - Ni Made Dhian Rani Yulianti; Ni Kadek Puteri Ari Darmayanti (Review of Management, Accounting, and Business Studies, 2020)
This study aimed to analyze the influence of discount and bonus pack towards impulse buying through hedonic shopping motivation at Indomaret Denpasar. The variables used were discount, bonus pack, hedonic shopping motivation, and impulse buying. The type of research used was a quantitative approach with the collecting data method using a questionnaire and sampling amounted to 99 respondents. The research location was conducted in Denpasar by using Indomaret consumers as the research object. The data analysis used in this study was partial least square. The test results showed that the discount had a significant positive effect on hedonic shopping motivation; the discount had no significant effect on impulse buying; the bonus pack had no significant effect on hedonic shopping motivation, bonus pack had a significant positive effect on impulse buying, and hedonic shopping motivation had a significant positive effect on impulse buying. In accordance with the form of sales promotion, bonus packs can affect consumers in making impulsive purchases. In this regard, the Indomaret minimarket must continue to focus and maintain sales promotions in increase sales promotions in the form of bonus packs. As well as other factors that will influence hedonists to shop for bonus pack.